Use of Physiological Parameters in Screening Drought Tolerance in Sugarcane Genotypes - de Almeida Silva, Marcelo [UNESP]; Jifon, John L.; Sharma, Vivek; da Silva, Jorge A.G.; Caputo, Marina M.; Damaj, Mona B.; Guimarães, Eduardo R.; Ferro, Maria I.T. [UNESP] (Springer Nature, 2011)
The physiological response of four commercial sugarcane genotypes to water stress was evaluated by measuring the photochemical efficiency of the photosystem II (chlorophyll a fluorescence ratio, F v/F m), estimated chlorophyll content (SPAD unit), leaf temperature (LT) and leaf relative water content (RWC). A field trial was established in the subtropical area with well-watered and water-stressed genotypes, in completely randomized blocks with four replicates in a 4 × 2 × 3 factorial design (genotype × irrigation × evaluation date). Physiological measurements were done during a 90 day-period of formative stage of plants. The analysis of variance showed that the interaction of genotype × irrigation × evaluation date had a significant effect for three physiological markers tested, F v/F m, SPAD unit and RWC. Under non-stressed conditions, all genotypes showed similar responses for the four markers. Under water deficiency stress, two drought-tolerant genotypes, HOCP01-523 and TCP89-3505 displayed higher values for F v/F m, SPAD unit and RWC, and lower values for LT, and could be classified as tolerant. It is therefore possible to use these physiological water stress associated traits as scorable marker traits for selecting drought-tolerant sugarcane genotypes in future breeding programs. © 2011 Society for Sugar Research & Promotion.
Keywords: Chlorophyll a fluorescence; Physiological markers; Saccharum spp.; Screening; Water stress; Saccharum